Shifting geo-economic power of the Gulf oil, finance and institutions - Legrenzi, Matteo; Momani, Bessma (The international political economy of new regionalisms series, 2011)
Investigates some of the 'new power brokers' in the world economy: the oil-exporting states of the Gulf. This title aims to fill this gap with a rigorous scholarly analysis based on primary sources and raw economic data. It brings together the expertise of academics who have devoted their career to careful study of the region.